Correction to: Swimming Program on Mildly Diabetic Rats in Pregnancy (Reproductive Sciences, (2021), 10.1007/s43032-021-00462-0) - Macedo, Nathália C. D. [UNESP]; Iessi, Isabela L. [UNESP]; Gallego, Franciane Q. [UNESP]; Netto, Aline O.; Sinzato, Yuri K. [UNESP]; Volpato, Gustavo T.; Zambrano, Elena; Damasceno, Débora C. [UNESP] (Springer Nature, 2021)
This article was updated to correct the affiliation numbers in the author display.